A Risky Business? - Kindler, Martha (IMISCOE Dissertations, 2011)
This book is about migration as a form of risk-taking. Based on Ukrainian women's experiences in the Polish domestic work sector, it presents a new approach to analyse movements of female migrants responding to the demand for household labour around the world. Risks involved in migration and in migrant domestic work are accounted for in detail alongside an analysis of the migration decision-making processes. This study shows how social ties and migrant institutions effectively reduce the otherwise radical asymmetry of power between an individual migrant, the state and an employer. A Risky Business? brings to light the complex risk structures of migrants' activities and their sophisticated responses to them. With their innovative strategies, migrants challenge government-imposed constraints and thus reduce the risks of migration.